PEMANFAATAN LIMBAH JERAMI, SEKAM, DAN URINE SAPI SEBAGAI PUPUK ORGANIK UNTUK MENINGKATKAN PERTUMBUHAN DAN PRODUKSI PADI - Istiqomah, Istiqomah; Eka Kusumawati, Dian; Dita Serdani, Army; Abdul Choliq, Fery (Universitas Islam Balitar, 2022)
Rice cultivation activities can produce organic waste such as straw and husks which can be processed into solid organic fertilizer and liquid smoke. In addition to agricultural waste, organic material from livestock waste can also be used as organic fertilizer, one of which is cow urine which can be processed into cow biourine. This research aimed to determine the effect of organic fertilizer from straw, husk and cow biourine on the growth and production of rice. The research used factorial randomized block design (RAKF) with 2 factors. The first factor is solid organic fertilizer which consists of treatment without solid organic fertilizer, straw ash, and rice husk biochar. The second factor is liquid organic fertilizer which consists of treatment without liquid fertilizer, cow biourine, and husk liquid smoke. The observed parameters were plant height, number of tillers, leaf chlorophyll content, number of panicles, weight of 1000 seeds, and weight of grain per hectare. The results showed that there was an interaction between solid organic fertilizer (rice husk biochar and straw ash) and liquid organic fertilizer (husk liquid smoke and cow biourine) in increasing plant height, number of tillers, number of panicles, and yields. Separate treatment of solid organic fertilizer and liquid organic fertilizer affected the leaf chlorophyll content of rice plants. The application of rice husk biochar and cow biourine fertilizer resulted in the highest plant height, number of tillers, and number of panicles. In rice yields, the highest yields were found in rice husk biochar combined with cow biourine and husk biochar combined with husk liquid smoke.